Pengaruh Waktu Perendaman Sabut Kelapa Dalam Ekstrak Kulit Batang Bakau Terhadap Intensitas warna dan Tahan Luntur dengan Fiksator Jeruk Nipis - Erika Ardila Arisandy; Vera Pangni Fahriani; Aulia Wahyuningtyas; Azafilmi Hakim (Jurnal Serambi Engineering, 2024)
Mangrove bark and coconut fiber can be used as natural dyes, because they contain tannin compounds, which are a natural brown color. The aim of this research was to determine the effect of soaking time for coconut fiber in mangrove bark extract on the color intensity and color fastness of washing soap on cotton fabric as well as the effect of lime fixator on soaking coconut fiber and mangrove bark extract. The process of extracting mangrove bark uses a water solvent, a ratio of raw materials to solvent of 1:10. The soaking process is within 24 hours and 48 hours. The fixation process is carried out by immersion technique. Color intensity test using a UV-2401 PC spectrophotometer and color fastness to soap washing using a gray scale standard. The research results showed that the smallest R% value or the lowest color intensity which produced the darkest color was the treatment of soaking coconut fiber in mangrove bark extract for 48 hours with or without a fixator. The lime fixator treatment shows a greater R% value, meaning that the lime fixator treatment produces a higher intensity or lighter color. The best color fastness after soaking coconut fiber for 48 hours with a score of 4-5 in the good category. Lime fixator can maintain the color fastness value of dyes that have absorbed into the fabric.